Nilai-Nilai Pendidikan Islam dalam Tradisi Bediom Rumah Adat Masyarakat Lampung Barat - Dendi Ari Sulendra; Husnul Mu'amalah; Saryati Purwanigara (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Indonesia is considered as a multi–ethnic country with cultural diversity because it has wide variety of tribes, cultures, religions and beliefs. Among the local wisdoms is the Bediom tradition carried out by Lampung Saibatin society. This tradition contains of various values, such as socio-cultural, religious, and Islamic educational value. This research was in form of descriptive analysis which is qualitatative in nature. The research aimed at to explore and analyze the Islamic value contained in Bediom, a traditional house in Lampung Saibatin society. The data were collected through observation, in-depth interview, and documentation. The data analysis is conducted through data reduction, data display, verification and conclusion drawing. The study found that the Bediom tradition of moving traditional house in Lampung Saibatin society implied Islamic educational values, such as the value ​​of monotheism (tauhid), shariah value, and moral value. These three values ​​of Islamic education can strengthen the local wisdom of the Lampung people which are rich in religious values. In addition, the bediom tradition which is full of moral values ​​can also strengthen social relations among multicultural societies. Thus, local wisdom that is full of religious values ​​should continue to be preserved.